Child labor and schooling response to changes in coca production in rural Peru - Ana C. Dammert (Institute for the Study of Labor (IZA), 2007)
Coca eradication and interdiction are the most common policies aimed at reducing the production and distribution of cocaine in the Andes, but little is known about their impact on households. This paper uses the shift in the production of coca leaves from Peru to Colombia in 1995 to analyze the indirect effects of the anti-coca policy on children's allocation of time. After different sensitivity checks, the results indicate that a decrease in coca production are associated with increases in work and hours children living in coca-growing states devote to work within and outside the household, with no effects on schooling outcomes. These findings suggest a previously undocumented indirect effect of drug policies on household behavior.
Keywords: 330; Koka; Pflanzenbau; Drogenpolitik; Haushaltsökonomik; Kinderarbeit; Bildungsverhalten; Peru